2003
DOI: 10.1128/jcm.41.4.1760-1762.2003
|View full text |Cite
|
Sign up to set email alerts
|

Drug-Associated Resistance Mutations in Plasma and Peripheral Blood Mononuclear Cells of Human Immunodeficiency Virus Type 1-Infected Patients for Whom Highly Active Antiretroviral Therapy Is Failing

Abstract: In 32 patients for whom highly active antiretroviral therapy was failing, a good agreement between drug resistance-associated mutations in plasma and peripheral blood mononuclear cells (PBMCs) was found (k ‫؍‬ 0.85). The mutations with the lowest agreement were 20R, 63P, and 84V in the protease gene and 184V in the reverse transcriptase gene. In eight patients, primary drug resistance mutations were detected only in PBMCs.The presence of resistant viral strains is routinely verified in plasma samples only, sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
15
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 10 publications
5
15
0
Order By: Relevance
“…A reasonable hypothesis is that DRMs persist at detectable levels longer in PBMC DNA than in plasma RNA due to the different rates of turnover of the virus in the two compartments (20). Indeed, discrepancies between drug resistance mutations in virus populations harbored in plasma RNA and PBMC DNA have been reported for subjects failing therapy as well as following cessation of treatment (24,27). Furthermore, drug resistance mutations were virtually identical in plasma RNA and PBMC DNA in the only study published so far on drugnaive subjects (5).…”
mentioning
confidence: 99%
“…A reasonable hypothesis is that DRMs persist at detectable levels longer in PBMC DNA than in plasma RNA due to the different rates of turnover of the virus in the two compartments (20). Indeed, discrepancies between drug resistance mutations in virus populations harbored in plasma RNA and PBMC DNA have been reported for subjects failing therapy as well as following cessation of treatment (24,27). Furthermore, drug resistance mutations were virtually identical in plasma RNA and PBMC DNA in the only study published so far on drugnaive subjects (5).…”
mentioning
confidence: 99%
“…Some studies reported more mutations in the plasma RNA (6,10,21,24), and others reported more mutations in the cellular DNA (14,34). Most of these discordances may be attributed to differences in the selection of the samples used for the evaluation.…”
Section: Continued On Facing Pagementioning
confidence: 93%
“…Results of published reports in this regard are very inconsistent (6,10,14,21,24,34). The present study aims to investigate both the possibility of DNA sequencing from whole blood cells or from DBS and the usefulness of DNA sequencing for determination of drug resistance in patients from a resource-poor setting with a high level of HIV-1 subtype diversity.…”
mentioning
confidence: 99%
“…Previous studies that have attempted to characterize the latent reservoir in viremic patients have not excluded the unintegrated viral DNA that predominates in the setting of high levels of viral replication (18,34,56). HIV-1 can enter resting CD4 ϩ T cells and undergo reverse transcription, but it cannot enter the nucleus to undergo integration into the host genome (6,53,63,71).…”
mentioning
confidence: 99%